Pembinaan Pemuda kristen tentang Pemuda, Teknologi dan Hamil diluar Nikah - Rohi, Januar D. M.; Sesfao, Maria I.; Sole, Adriana I.S.; Dethan, Yandri D. (Institut Agama Kristen Negeri Kupang, 2024)
Youth are the backbone of a nation as well as a church, therefore as youth they should do many things in life, and be the controllers of the rapid technological advances that are currently developing. However, in reality, with the advancement of existing technology, many young people fall into promiscuity (extramarital sex) which causes pregnancy. Because young people in the era of introducing technology, are still unable to control themselves well, they actually fall into habits that are detrimental to themselves, others, and society. The purpose of this community service activity is to provide education and encouragement for young people in Siloam Humone so that they can know and understand the benefits and impacts of using technology, and be wise in using technology, so that they do not fall into promiscuity. The method of implementing PKM